2019
DOI: 10.1016/j.bej.2019.107265
|View full text |Cite
|
Sign up to set email alerts
|

Purification and polymerisation of microbial d-lactic acid from DDGS hydrolysates fermentation

Abstract: A multi-step process was developed for microbial D-lactic acid purification, followed by poly-D-lactic acid (PDLA) synthesis via azeotropic polycondensation process. Several anion exchange resins were screened for their binding capacity using model lactic acid solutions. Amberlite ® IRA67 (weak base anion exchange resin) showed the highest lactic acid adsorption, with maximum adsorption capacity, qmax, of 136.11 mg lactic acid / g of resin, and was further selected to purify D-lactic acid from DDGS hydrolysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In the conventional lactic acid recovery process, impurities that remained in the fermentation broth were removed before lactic acid recovery by ion exchange resins to ease the separation process (Lee et al 2017 ). The remaining glucose in the fermentation broth was typically removed by nanofiltration (Alvarado-Morales et al 2021 ; Zaini et al 2019 ). Lately, some weakly polar ion exchange resin such as HD-06 was used to adsorb glucose from the fermentation broth before the adsorption of lactic acid and anions by the anionic ion exchange resins such as Lewaitit S3428 (Song et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the conventional lactic acid recovery process, impurities that remained in the fermentation broth were removed before lactic acid recovery by ion exchange resins to ease the separation process (Lee et al 2017 ). The remaining glucose in the fermentation broth was typically removed by nanofiltration (Alvarado-Morales et al 2021 ; Zaini et al 2019 ). Lately, some weakly polar ion exchange resin such as HD-06 was used to adsorb glucose from the fermentation broth before the adsorption of lactic acid and anions by the anionic ion exchange resins such as Lewaitit S3428 (Song et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The operation is simple and easy to scale up. Previous studies reported that cationic and anionic ion exchange resins such as Amberlite IRA-96, Amberlite IRA-67, and Amberlite IRA-120 were used to recover organic acid (Bayazit et al 2011 ; Bishai et al 2015 ; Zaini et al 2019 ). Adsorption using polymeric ion exchange resins to recover the desirable product consists of 5 major steps including pretreatment of the resins, adsorption, washing, desorption, and resin regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Zaini et al [31] also started LA purification using a strong acid cationic resin (IRA 120) to convert the lactate salt into LA. Due to the functional groups of sulfonic acid, theoretically, the hydrogen ions (H + ) that are linked to the functional group of the resin will bind to the sodium lactate obtained at the end of the fermentation, and convert it into LA.…”
Section: La Purification Using Cationic and Anionic Resins (Glass Col...mentioning
confidence: 99%
“…Zaini et al ., in one of the most recent studies, developed a multi‐step process for lactic acid purification and poly‐ d ‐lactic acid synthesis with an azeotropic poly‐condensation process. The authors used weak anion exchange resins (Amberlite® IRA67 and Diaion® WA30) and strong anion exchange resins (Amberlite® IRA400 and Dowex® Marathon™ MSA).…”
Section: Separation Of Lactic Acid By Ion Exchangementioning
confidence: 99%